Achieving sustainable development : the challenge of governance across social scales - Bressers, Hans; Rosenbaum, Walter A.
Bressers, Rosenbaum, and their contributors analyze what, until recently, has been among the least examined issues implicit in the growing global discourse about sustainable development: the creation of institutions and processes for effective governance of sustainability policies. The creation and endurance of governance institutions capable of implementing sustainability policies is, in fact, fundamental for any viable conception of sustainable development. The analyses focus not only on how societies can organize, but on how they do organize to overcome such daunting obstacles in the Nether.